Implementasi Google Clasroom dalam Pembelajaran Pendidikan Agama Islam pada Masa Pandemi Covid-19 - Humayrah Humayrah; Alfurqan Alfurqan (Prodi Pendidikan Keagamaan Islam, 2022)
The purpose of this study was to determine the implementation of google classroom in Islamic religious education learning during the covid-19 pandemic in class IX-1 SMP N 5 Mandau, with learning carried out from home requiring educators to be more intelligent in carrying out the teaching and learning process, so from Google Classroom is one of the media that is widely used by educators. This type of research uses a descriptive qualitative approach, the data sources in this study include primary data sources and secondary data sources, the methods used in this research are observation, interviews, and documentation. Data analysis with data reduction, data presentation, and drawing conclusions. To analyze the data, the researchers used triangulation of different sources. The results of the research that was carried out at SMP N 5 Mandau, the researchers found that PAI teachers had used Google classroom well according to the learning implementation plan that had been implemented, although there were still some obstacles from schools, educators, and students.